DINAMIKA SOSIAL KEAGAMAAN MAJELIS TAFSIR AL-QURAN (MTA) PUSAT DI KOTA SURAKARTA JAWA TENGAH - Wakhid Sugiyarto (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
In Surakarta city occur the dynamics which lead to tensions and conflicts caused by the incessant propaganda by Tafsir Qur’an Assembly (MTA). This research is necessary, to understand and manipulate the social condition in order to create harmonious and tolerant situation. Focuses of the research are the historical development of MTA, propagation models, developed basic teachings and religious leaders and the government’s responses to MTA. Social religious fidgetiness and tension due to the appearance of MTA indicated caused by the immature attitude and horizon of thinking of the society, especially the bottom stream of society (grassroots). They would hear the appeal of religious scholars (kyai) rather than to forward the reasoning of logical thinking. The conflict was caused by the self-defense expression, backed into a corner and then hit back with physical and rhetoric. This study used a qualitative approach.